2011
DOI: 10.1258/jms.2011.011081
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality-of-life in children with coeliac disease, measured prior to receiving their diagnosis through screening

Abstract: The HRQoL reported by 12-year-olds with screening-detected CD, before they learned of their diagnosis, was not worse than that of the children without CD or those previously diagnosed with CD. Thus, mass screening for CD should not be justified on the basis that children with unrecognized CD have a poor HRQoL. However, because these children rated their HRQoL before diagnosis and treatment, they may not have recognized or perceived symptoms as severe enough to seek medical attention which demonstrates how diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 36 publications
1
23
0
1
Order By: Relevance
“…However, when considering the QOL of screen-detected patients with CD, the current evidence is limited and conflicting. While some studies showed no differences in HRQOL (equally at diagnosis and after starting the GFD), between adolescents with screen-detected CD and their healthy controls or symptomatic CD patients [18][19][20], another UK study demonstrated that 27% of screen-detected patients completely regretted being diagnosed with CD, therefore questioning the acceptability of the treatment and screening procedures [21]. Furthermore the positive impact of the GFD on Physical Health could be related to a significantly higher energy intake in patients on GFD than controls, with no impact on body mass index [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, when considering the QOL of screen-detected patients with CD, the current evidence is limited and conflicting. While some studies showed no differences in HRQOL (equally at diagnosis and after starting the GFD), between adolescents with screen-detected CD and their healthy controls or symptomatic CD patients [18][19][20], another UK study demonstrated that 27% of screen-detected patients completely regretted being diagnosed with CD, therefore questioning the acceptability of the treatment and screening procedures [21]. Furthermore the positive impact of the GFD on Physical Health could be related to a significantly higher energy intake in patients on GFD than controls, with no impact on body mass index [22].…”
Section: Discussionmentioning
confidence: 99%
“…A previous population based study from our group, found no HRQoL difference between 153 school aged children with undetected celiac disease and children without celiac disease, when investigating self-reported HRQoL by the shorter six item EQ-5D-Y HRQoL instrument [29]. In the current study we confirmed these results in an extended study group (238 12-year old children with undetected celiac disease) and by use of a more comprehensive assessment of HRQoL (full-form 52 item Kidscreen instrument).…”
Section: Discussionmentioning
confidence: 99%
“…All children were invited to provide a blood sample and alongside to fill in a questionnaire. Data collection was performed in the schools by research nurses with assistance from school health nurses and teachers [16,29]. Afterwards, blood samples were analyzed for serological markers; anti-tissue-transglutaminase antibodies of IgA-type (tTG) for all children and for some also anti-endomysial antibodies IgA (EMA), or in case of IgA-deficiency serological markers of IgG type.…”
Section: Methodsmentioning
confidence: 99%
“…Studies involving the same children as in the current study showed that, before knowledge of CD status, the screening-detected CD children reported similar health-related quality of life as their peers. 25 One year after diagnosis, 72% strictly complied with the diet and 54% subjectively perceived improved health, but at the same time they described social sacrifices in relation to the diagnosis and treatment. 21 Nevertheless, mass screening seemed to be acceptable to most of those being diagnosed and their parents.…”
Section: Figurementioning
confidence: 99%